Graves Disease: Diagnosis dan Tatalaksana - Fatikha Rudia Ahda; I Gede Aditya Satrya Bhuwana Cakra; Ni Made Sri Padma Puspita; Eva Triani; Lestary, Ayundha Rizky (Faculty of Medicine, Universitas Mataram, 2023)
Abstract: Hyperthyroidism is an increase in the amount of thyroid hormone synthesis and secretion by the thyroid gland. Graves Disease (GD) is the most common cause of hyperthyroidism. Graves Disease (GD) is more common in women than men and in patients with a family history of GD. Graves Disease can also be triggered by environmental factors such as stress, smoking, infection, and exposure to iodine. Graves Disease manifests in the form of the Merseburger triad consisting of thyrotoxicosis, diffuse goiter, and ophthalmopathy (orbitopathy) with symptoms of agitation, palpitations, and muscle weakness. In making the diagnosis of GD, 2 tests are carried out, namely a thyroid function test which consists of examinations to diagnose hypothyroidism, namely Wayne index scoring, TSH test, and FT4 as well as tests to distinguish GD from other causes of hyperthyroidism, namely TRab, radioactive iodine uptake scan with I-123 or I-131, thyroid ultrasound with doppler, T3/T4 ratio values, and CT or MRI. The goal of treatment for GD is to control and improve the condition based on the pathophysiology of GD, namely the antigen-antibody reaction in the thyroid gland. Modalities for the treatment of GD consist of anti-thyroid drugs, surgery, and radioactive iodine (RAI) treatment with sodium-131(131I). The choice of treatment is based on the severity of thyrotoxicosis, age, thyroid size, availability of modalities, response to treatment, and other comorbidities.